EFFECTIVENESS OF HOTS-BASED GAME-BASED LEARNING ON CRITICAL THINKING ABILITIES AND NUMERATION LITERACY OF GRADE IV STUDENTS OF LAMBUNU ELEMENTARY SCHOOL, PARIGI MOUTONG DISTRICT - Ayu Ashari; Besse Nurul Hikmah; Sahrul Syawal (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effectiveness of Higher Order Thinking Skills (HOTS)-based game-based learning on the critical thinking ability and numeracy literacy of fourth-grade students at SDN Lambunu, Parigi Moutong Regency. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The sample consisted of 56 students divided into experimental and control groups. Research instruments included validated critical thinking and numeracy literacy tests. Data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, independent sample t-test, and N-gain score. The results revealed significant differences between the two groups in critical thinking (t = 9.847; p = 0.000) and numeracy literacy (t = 10.213; p = 0.000). The experimental group's posttest mean was substantially higher than the control group on both variables. The experimental group's N-gain scores of 0.61 and 0.60 fell within the moderate category, whereas the control group remained in the low category. It is concluded that HOTS-based game-based learning is proven effective in improving elementary students' critical thinking and numeracy literacy, and is worthy of broader implementation in primary education, particularly in remote area contexts.